REPRESENTASI GENDER DALAM NOVEL “CATATAN HATI SEORANG ISTRI” KARYA ASMA NADIA (KAJIAN FEMINISME) - Wahyu Mamik Ika Sukmawati (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2019)
The purposes of the research were (1) to describe injustice of a woman or wife (2) to describe a struggle of a woman or wife (3) to describe the effect of injustice toward a woman or wife. Then, it would be the first step in struggling prespective of gender and to complete the analysis of gender injustice.This research used descriptive qualitative method that explained all element about the kinds of method and the approach. The data of the research were quotes, description, and expression which consist of norm in Catatan Hati Seorang Istri novel by Asma Nadia. In data analysis, the writer used a descriptive analysis and a content analysis and also the conclusions.The result of the research was carried out to show that the Catatan Hati Seorang Istri novel had many stories about exploitation of aman or husband toward a woman or wife and the struggle of a woman or wife to her rights.Based on the research, it could be concluded that a woman or wife still had ability to struggle her rights. Therefore, it supposed to a woman or wife not to doubt in struggling the gender equality.